Detection and Characterization of the Grindulu Fault Using TOPEX Satellite Gravity Data: SVD Analysis in the Pacitan Region, East Java - Realita, Arie; Fahmi, Muhammad Nurul; Madlazim, Madlazim; Maulidah, Hikmatul; Anggraeni, Firdha Kusuma Ayu; Chasanah, Uswatun (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The southern part of Java Island is dominated by a volcanic arc system associated with the subduction of the Indo-Australian Plate beneath the Eurasian Plate. This tectonic setting results in a structurally complex region with active fault systems that contribute to an elevated seismic hazard in southern East Java. One prominent structure in this region is the Grindulu Fault in Pacitan Regency, whose trace geometry and subsurface expression remain debated. In this study, we use gravity data to delineate the Grindulu Fault corridor and constrain its spatial configuration. Gravity anomaly data derived from TOPEX satellite observations were corrected to produce Complete Bouguer Anomaly (CBA) values. The CBA data were gridded using kriging with a spacing of Δx = 1 km (≈0.01°). To separate regional and residual components, the Second Vertical Derivative (SVD) method was applied directly to the gridded data, enhancing short-wavelength features while suppressing long-wavelength regional anomalies. Structural boundaries were identified based on continuous NE–SW lineaments characterized by SVD zero-crossings with adjacent positive–negative extrema. The inferred Grindulu Fault is expressed as a NE–SW trending corridor extending approximately between 111.11°–111.28°E and 8.04°–8.15°S. The SVD asymmetry observed along several profiles is consistent with a normal-fault-like density contrast geometry in some sections and a strike-slip fault behavior in others. However, fault kinematics cannot be uniquely determined from gravity-derived derivatives alone without independent geological or seismological validation. Overall, the results provide a reproducible gravity-based constraint on the Grindulu Fault corridor, offering valuable insights for future seismotectonic interpretations and disaster risk reduction planning in southern Java.